Seawater carbonate chemistry and growth and physiology of strain CCMP 1334 of the marine cyanobacterium Synechococcus (Cyanophyceae) - Sharbaugh, Alyssa K; Laws, Edward A (PANGAEA, 2025)
The marine cyanobacterium Synecococcus sp. (CCMP 1334) was grown in a continuous culture system on a 12:12 h light:dark cycle at all combinations of low and high pCO2 (400 and 1000 ppmv, respectively), nutrient availability (nitrate-limited and nutrient-replete conditions), and temperatures of 21, 24, 28, 32, and 35°C. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were extracted from tables in the related paper (see Related to) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2024-12-23.
Keywords: Bacteria; Biomass/Abundance/Elemental composition; Bottles or small containers/Aquaria (<20 L); Cyanobacteria; Growth/Morphology; Laboratory experiment; Laboratory strains; Macro-nutrients; Not applicable; Pelagos; Phytoplankton; Primary production/Photosynthesis; Respiration; Single species; Synechococcus sp.; Temperature